Cyclic Peptide Extracts Derived From Pseudostellaria heterophylla Ameliorates COPD via Regulation of the TLR4/MyD88 Pathway Proteins - Lu, Feng; Yang, Han; Lin, Si-ding; Zhao, Li; Jiang, Chang; Chen, Zhi-bin; Liu, Ying-ying; Kan, Yong-jun; Hu, Juan; Pang, Wen-sheng (Frontiers in Pharmacology, 2020)
To explore the method of extraction and purification of cyclic-peptide extract (CPE) and characterize the structure of the compounds, we investigated the biological activity of CPE from Pseudostellaria heterophylla (Miq.) Pax. (Taizishen, TZS) attenuating chronic obstructive pulmonary disease (COPD) in rats. The CPE from TZS was obtained by ethyl acetate, petroleum ether, hot water extraction, and alcohol-precipitation. Cyclic-peptide structures were distinguished using ultra-high performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MS/MS). Rats were induced by solid combustibles smoke (SCS) for the COPD model, and the attenuation of COPD activity by CPE was detected using lung airway resistance and dynamic lung compliance, as well as pulmonary tissue hematoxylin and eosin (HE) staining. The relevant inflammatory cytokines were assayed by enzyme-linked immunosorbent assay (ELISA). CPE obtained from TZS contained 12 cyclic-peptide constituents; the purity was up to 92.94%. CPE (200, 400, or 500 mg/kg/day) was given to SCS-induced COPD model rats orally for 15 days. The results showed that in rats given CPE (400 mg/kg/day) there was a sharp fall in lung airway resistance but a rise in dynamic lung compliance. The image analysis of lung tissue sections suggested that CPE could decrease the degree of alveolar destruction (p < 0.05), alleviate lung inflammation, increase alveolar space, and improve the infiltration of inflammatory cells. CPE was found to reduce serum levels of tumor necrosis factor (TNF-α), but increase interleukin-10 (IL-10), adjusting multiple cytokines. The expression levels of TLR4 mRNA and MyD88 mRNA, and p-JNK and p-p38 N were significantly down regulated in rat alveolar macrophages. CPE intervention could improve pathological changes of the pulmonary ventilation function in COPD rats, which may be related to its effect in inhibiting the abnormal activation of the TLR4-MyD88-JNK/p38 pathway. This is the first report that the CPE of TZS lessens the severity of COPD episodes. The new preparation process of CPEs implements the anticipated goal, which is to refine CPE and actualize quality control.